The possibility of utilization of soy straw powder in wood/plastic composites produced with polypropylene - Abolfazl Kargarfard (Regional Information Center for Science and Technology (RICeST), 2015)
Abstract The objective of this study was to produce natural fiber –plastic composite using soy straw powder as reinforcing component and to investigate the effect of nano-clay particles addition on the mechanical properties of the composite. Two levels of soy straw powder (35 and 45%) based on the weight of the composite, three levels of nano-clay (0,3 and 6%) based on the weight of the polypropylene as the matrix was used. Five percent Maleic Anhydride Ploy Propylene (MAPP) was added as the coupling agent. Composites compound was made and then